Flock-Level Seroprevalence Against Ornithobacterium rhinotracheale among Broilers in Uruguay - Suzuki, K.; Petruccelli, M.; Trenchi, G.; Giossa, G.; Rodriguez, G.; Trenchi, H. (International Journal of Poultry Science, 2010)
The objective of this study was to estimate the true prevalence of seropositive broiler flocks against Ornithobacterium rhinotracheale in Uruguay, South America. Seventeen farms of broiler chickens greater than 35 days of age were studied. The field investigation was conducted between October 2008 and April 2009. Individual-chicken sera and pooled sera (containing 10 individual-chicken sera each) were analyzed using a commercial ELISA for the detection of antibody against Ornithobacterium rhinotracheale in chicken serum. A total of 181 pooled samples from the study area representing 17 farms were examined. Fifty-four pools were classified as test positive, because they included at least one individual-chicken classified as positive. On the basis of deterministic approach, the estimates for the apparent prevalence and true prevalence at flock-level were 30% and 17%, respectively. The true prevalence estimate with the Bayesian model (stochastic approach) was slightly lower and having wider confidence intervals [11% (95% CI: 0%-32%)].